Pollution source identification methods and remediation technologies of groundwater: A review - Ya-ci Liu; Yu-hong Fei; Ya-song Li; Xi-lin Bao; Peng-wei Zhang (China Geology, 2024)
Groundwater is an important source of drinking water. Groundwater pollution severely endangers drinking water safety and sustainable social development. In the case of groundwater pollution, the top priority is to identify pollution sources, and accurate information on pollution sources is the premise of efficient remediation. Then, an appropriate pollution remediation scheme should be developed according to information on pollution sources, site conditions, and economic costs. The methods for identifying pollution sources mainly include geophysical exploration, geochemistry, isotopic tracing, and numerical modeling. Among these identification methods, only the numerical modeling can recognize various information on pollution sources, while other methods can only identify a certain aspect of pollution sources. The remediation technologies of groundwater can be divided into in-situ and ex-situ remediation technologies according to the remediation location. The in-situ remediation technologies enjoy low costs and a wide remediation range, but their remediation performance is prone to be affected by environmental conditions and cause secondary pollution. The ex-situ remediation technologies boast high remediation efficiency, high processing capacity, and high treatment concentration but suffer high costs. Different methods for pollution source identification and remediation technologies are applicable to different conditions. To achieve the expected identification and remediation results, it is feasible to combine several methods and technologies according to the actual hydrogeological conditions of contaminated sites and the nature of pollutants. Additionally, detailed knowledge about the hydrogeological conditions and stratigraphic structure of the contaminated site is the basis of all work regardless of the adopted identification methods or remediation technologies.©2024 China Geology Editorial Office.